Analisis Kesalahan Penggunaan Partikel Ni dan De - Marion, Elisa Carolina (Bina Nusantara University, 2008)
Articel clasified the type and cause of mistake done by Bina Nusantara Japanese student of six and eight semesters on the use of ni (ã«) and de (ã§) particles indicating place in the exam. Data were collected from library research and distributed questionnaires to 79 student of the 6th and 8th semester, Japanese departement. The result showed that the student of Japanese language did not make the same mistake in using the ni (ã«) and de (ã§) particles having the some function in indicating place. It is concluded that the respondents are able to use the ni (ã«) and de (ã§) particles.Â Â Â Â Â Â